A Multi-Index Evaluation of Drought Characteristics in the Yarlung Zangbo River Basin of Tibetan Plateau, Southwest China - Niu, Qiankun; Liu, Liu; Heng, Jingxia; Li, Hao; Xu, Zongxue (Frontiers in Earth Science, 2020)
The Yarlung Zangbo River (YZR) basin occupies a crucial position in the formation and development of atmospheric circulation and climate change in the Tibetan Plateau, where is the potential trigger and amplifier in global climate fluctuations. Previous studies mainly focused on meteorological drought induced by variations of precipitation and temperature. In this study, a multi-index evaluation of drought characteristics from the perspective of meteorology and agriculture was implemented. GLDAS (Global Land Data Assimilation System) precipitation, surface air temperature and soil moisture data from 1982 to 2015 were used to calculate the meteorological drought index (Standardized Precipitation Evapotranspiration Index) and agricultural drought index (Soil Water Deficit Index), respectively. Meanwhile, the scPDSI (self-calibrating Palmer Drought Severity Index) dataset provided by CRU (Climate Research Unit) was also utilized to represent the meteorological drought, with the aim of comprehensively investigating the spatiotemporal evolution characteristics of drought in the YZR basin. Results indicated that although there was a slightly wetting tendency of the whole basin from 1982 to 2015, drought condition from the perspective of meteorology and agriculture at both annual and growing seasonal scales showed a transition from alleviation to aggravation during 1982–2015, with an abrupt change from wetting to drying occurring at the year of 2000 detected by multiple statistical tests including Mann-Kendall test, Moving t-test and Yamamoto test. Specifically, since the twenty-first century, the meteorological drought in the YZR basin has changed from moderate wet to moderate dry, while the agricultural drought relieved to moderate dry from severe dry with a much more complicated fluctuation. From the perspective of spatial pattern, the annual and growing season variation trends of all three drought indices were identically consistent during 1982–2015. Areas with extremely significant decreasing trend (2.24 21.09%) were mostly distributed in the west upstream and southwest downstream dominating the overall wetting trend of the YZR basin during the period of 1982–2015, while the transition from wet to dry after 2000 was attributed to the aggravating drought of the western upstream and southeastern downstream. Results of this study have important implications for drought monitoring and eco-environmental sustainability in alpine regions.